1998
DOI: 10.1111/j.1475-6811.1998.tb00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive illusion in close relationships

Abstract: The literature regarding self‐other comparisons suggests that self‐enhancing perceptions are prevalent, including forms of “illusion” such as excessively positive self‐evaluation, unrealistic optimism, and exaggerated perceptions of control. Concepts from optimal distinctiveness theory served as the basis for two experiments examining whether illusion functions similarly when the context of evaluation involves a relationship. In both experiments participants rated themselves, the best friend, and the average o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 81 publications
6
88
1
Order By: Relevance
“…The present For example, people believe that their own current romantic relationship is better than other romantic relationships (e.g., Fowers, Lyons, & Montel, 1996;Fowers, Lyons, Montel, & Shaked, 2001;Martz et al, 1998;Van Lange & Rusbult, 1995), have idealized memories about past events in their current romantic relationship (e.g., Fletcher & Kerr, 2010;Karney & Coombs, 2000;Karney & Frye, 2002), have an illusion of control over their romantic relationship (e.g., Murray & Holmes, 1997), and overestimate their own similarity to their romantic partner (e.g., Murray, Holmes, Bellavia, Griffin, & Dolderman, 2002). These phenomena are not directly relevant for the present paper and will therefore not be discussed further in this article.…”
Section: Resultsmentioning
confidence: 99%
“…The present For example, people believe that their own current romantic relationship is better than other romantic relationships (e.g., Fowers, Lyons, & Montel, 1996;Fowers, Lyons, Montel, & Shaked, 2001;Martz et al, 1998;Van Lange & Rusbult, 1995), have idealized memories about past events in their current romantic relationship (e.g., Fletcher & Kerr, 2010;Karney & Coombs, 2000;Karney & Frye, 2002), have an illusion of control over their romantic relationship (e.g., Murray & Holmes, 1997), and overestimate their own similarity to their romantic partner (e.g., Murray, Holmes, Bellavia, Griffin, & Dolderman, 2002). These phenomena are not directly relevant for the present paper and will therefore not be discussed further in this article.…”
Section: Resultsmentioning
confidence: 99%
“…Some investigators have examined illusion by assessing whether individuals evaluate their partners more favorably than the partner evaluates the self (Murray et al, 1996a(Murray et al, , 1996b. Other investigators have examined illusion by assessing whether individuals evaluate their own relationships more favorably than they evaluate others' relationships (Buunk & Van Yperen, 1991;Martz et al, 1998;Murray & Holmes, 1997). However, far fewer studies have examined the motivational properties of illusion by means of the direct manipulation of motives.…”
Section: Motivational Properties Of Perceived Superioritymentioning
confidence: 99%
“…Research regarding the self has identified three primary forms of positive illusion, demonstrating that we exhibit excessively positive self-evaluations, exaggerated perceptions of control, and unrealistic optimism regarding the future (for reviews, see Taylor & Brown, 1988;Wood, 1989). The empirical literature reveals parallel phenomena in close relationships, demonstrating that we exhibit excessively positive evaluations of our partners and relationships, exaggerated belief in the controllability of our relationships, and unrealistic optimism regarding the future of our involvements (Buunk & Van Yperen, 1991;Martz et al, 1998;Murray & Holmes, 1993, 1997 The present research examines a phenomenon termed perceived superiority, which is defined as the inclination to regard one's own relationship as both better than and not as bad as other people's relationships: This work is based on the assumption that we do not experience our relationships in a vacuum: Although beliefs about a relationship are shaped in part by the good and bad properties of the relationship per se, beliefs are also socially defined. That is, we also understand and experience our involvements in relation to the beliefs we hold about the good and bad properties of other people's involvements.…”
mentioning
confidence: 99%
“…For example, a study by Srivastava, McGonigal, Richards, Butler, and Gross (2006) shows how trait-optimism-the disposition to expect positive outcomes-makes positive outcomes like satisfaction, feeling supported, and resolving conflicts more likely in romantic relationships. Relatedly, there is a large body of literature about the role of positive illusions in relationships (e.g., Martz et al, 1998;Murray & Holmes, 1997;Murray, Holmes, & Griffin, 1996a, 1996b which is very much in-line with the self-fulfilling prophecy paradigm cited above as an exemplar of interactionism. 17 These are but a few examples from a much larger body of work which offers one of the most promising future directions for the extended cognition research program.…”
Section: New Directionsmentioning
confidence: 78%